Gaelic in Scotland : policies, movements, ideologies - McLeod, Wilson (Edinburgh University Press, 2020)
In this extensive study of the changing role of Gaelic in modern Scotland, Wilson McLeod looks at the policies of government and the work of activists and campaigners who have sought to maintain and promote Gaelic.